Ṣināʿat al-kitāb wa-al-kitābah fī al-Ḥijāz: ʿAṣr al-Nubūwah wa-al-khilāfah al-rāshidah = Book making and writing in the Hijaz : era of the Prophet and the Rashidun caliphate - Bādaḥdaḥ, Mājid ibn ʿAbbūd (Makkah al-Mukarramah ʿāṣimat al-thaqāfah al-Islāmīyah 1426 H (2005 M), 2006)
Arabic writing; publishing; Saudi Arabia; history